(3GdLGeY GdUMjMs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3HGH MQb GdOhQ hGdfNjd s
(3BNQgG (B:s
(3BNQ GdLRA GdNGeS ef JLRFI YTQI CLRGA ef UMjM GdHNGQi QMeg Gddg s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3YdjgG ebGHdGJs
(3YdjgG hba hJedcs
(3bQFJ Ydi RcQjG GdCfUGQi hZjQg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
Keywords: (3GdMOjK h GdeUWdMs